Sistem Hukum Perkawinan Masyarakat Adat Baduy Desa Kanekes Kecamatan Leuwidamar Provinsi Banten - Retno Untari (Fakultas Syariah IAIN Laa Roiba Bogor, 2019)
The purpose of this research is to find out and discuss the Baduy Indigenous Marriage Legal System of Kanakes Village, Leuwidamar Subdistrict. This research and writing were prepared and compiled using empirical research methods using qualitative analysis, namely by conducting direct interviews with Jaro (Head of the Village) and the Baduy indigenous community. Marriage is a natural law that must occur and be carried out by every human being without exception. The legal system of marriage to the Baduy indigenous people, that is Monogamy marriage, which means that a Baduy man cannot have more than one wife and polygamy marriage is a taboo subject. In addition, the factors that influence the Baduy indigenous community's compliance with customary law include religious and religious factors, social and cultural factors, customary law and religious factors. Keywords: legal system, marriage, community, traditional baduy